FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PELAKU UMKM UNTUK MENGGUNAKAN APLIKASI AKUNTANSI BERBASIS SELULER DI DUSUN BUGEL SAMPANG KABUPATEN CILACAP - Anis Astiyah; Martinus Budiantara (Jurnal Akuntansi dan Keuangan (JAK), 2023)
Advances in information technology provide opportunities for MSME actors to develop their business through the integration of information technology in business processes. With this, recording of financial data can also be done online via the web or even via a smartphone, because many financial recording applications have been launched based on Android Mobile to make it easier for users, especially for MSME. This study aims to determine whether social influences, facilitating conditions, perceived trust, and technology anxiety affect the interest of MSME to use mobile accounting applications. The method used in this study is a quantitative method with data collection techniques through questionnaires. The results of the study show that social influences and facilitating conditions influence the interest in using mobile accounting applications. Meanwhile, perceptions of trust and technology anxiety have no effect on the intention to use mobile accounting applications.